Collocation Use in EFL Learners’ Writing Across Multiple Language Proficiencies: A Corpus-Driven Study - Du, Xiangtao; Afzaal, Muhammad; Al Fadda, Hind (Frontiers in Psychology, 2022)
This paper examines the linguistic features of collocation use by learners demonstrating different levels of proficiency. It also explores possible properties of the collocations which may help predict their difficulty level. Making use of regular expressions and the Python programming language, we extracted make/take + noun collocations in the learner corpus EFCAMDAT. Next, adopting a corpus-driven approach underpinned by a systematic and reliable framework for evaluating collocation competence and determining difficulty level, we examined the collocations used by the learners. The study found developmental patterns in the learners’ productive collocational knowledge about the semantic fields of noun elements in collocation and syntactic sequences which are likely to indicate the difficulty level of the collocation. The difficulty levels and the length of noun elements in collocation were found to manifest a rather weak positive association with learners’ proficiency levels. Further, the qualitative analysis of data revealed the error types prevalent in learners’ collocation use.